A STUDY TO ASSESS THE EFFECTIVENESS OF INFORMATION BOOKLET ON KNOWLEDGE AND PRACTICES REGARDING PREVENTION OF VARICOSE VEIN AMONG THE SELECTED GROUP OF PEOPLE OF GUWAHATI, ASSAM. - Thongbam, Rojibala; Ranju Rani Das,; Manju Chapagain, (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2020)
Background: Lower limb varicose veins are common and known to have a  higher prevalence among people who work in occupations requiring prolong standings. Varicose veins are a common chronic venous disorder affecting 20 to 60% of adults worldwide [1,2,3]. Approximately 23% of the US adults have Varicose veins. [4]. The extrapolated prevalence rate of varicose vein in India providing warning is about 47,928,177 in statistics.[5] Varicose vein in the legs can be complicated by, Chronic venous ulcerations, venous thromboembolism and haemorrhage from ruptured.[6] Aim: The aim of the study was to assess the effectiveness of information booklet on knowledge and practices regarding prevention of varicose vein among the selected group of people of Guwahati, Assam.  Method and Material: The research approach adopted for the study was quantitative approach. Pre experimental one group pre-test post-test design was used in this study . Purposive sampling technique was used to select the samples. The sample size was 90 peoples (30 shopkeepers, 30 hairdressers  and 30 security guards) who fulfilled the inclusion criteria. Study were conducted in selected hospital, local beauty parlour and local shop in Guwahati, Assam. Pretest knowledge and practices were checked with semi structured questionnaires and inventory checklist respectively and post test was conducted after 7 days in the same manner. The technique used was self report. Results: Out of 90 respondents, the mean knowledge score before and after intervention were 6.2 and 13.71 respectively. The mean practices score before and after intervention were 3.45 and 6.85 respectively. The information booklet was proved effective where the calculated value of  ‘Z’ (13.12) and (16.19)  was more than the tabulated value (2.33) at 0.01% level of significance. So, it signifies that the information was effective as it increase the post test level of knowledge and practices. There was no significant association between pre test knowledge with selected demographic variables whereas there was significant association between pretest practices with selected demographic variables such as Age and working experience. The calculated ‘r’ value for pretest knowledge and practices, r= 0.62, and post test knowledge and practices, r= 0.42 showed there was moderately positive correlation. Conclusion: This study showed that after giving information booklet there was an improvement in the knowledge score and practices score, suggestive of effectiveness of the information booklet on prevention of varicose vein. Hence awareness program in regular period will help in gaining knowledge and practices regarding prevention of varicose vein among high risk people to have a healthy society